Thermal comfort conditions of a small-scale tropical enclosed giant freshwater prawn (Macrobrachium rosenbergii) hatchery: a case study - Zolkefli, Emy Yusliza; Sheikh Ahmad, Sabarinah; Kamarudin, Mohd Salleh; Saad, Che Roos; Ja'afar, Mohamad Fakri Zaky; Othman, Jamarei (Academic Journals, 2011)
This study was conducted to determine the thermal comfort conditions of a typical small-scaled enclosed freshwater prawn hatchery building. The thermal environment and comfort conditions were determined using in situ measurement for 12 continuous days and simulations. A small-scaled commercial hatchery at Sg Besar, Selangor was chosen for this study. The multi-data loggers were placed in selected area of hatchery building and the parameters measured were temperature (indoor, outdoor and water), light (indoor and water) and Relative Humidity (RH) (indoor and outdoor). The results showed that the indoor air temperature remained above comfort limit temperature (28.6°C) between 0900 and 1900 h beyond the working period (0700-1900 h). The water temperature remained above the optimal culture temperature (30°C) and reached the lethal limit (33°C) during the day. The average indoor relative humidity fell below outdoor relative humidity over the most of daytime and above the outdoor relative humidity at nighttime. The results indicated that daytime thermal environment in the hatchery building was extremely uncomfortable to the workers most of the time and at certain time could also detrimental to larval prawn growth.